Synthesis, characterization, third-order non-linear optical properties and DFT studies of novel SUBO bridged ball-type metallophthalocyanines - GÖRK, GÜLŞEN; ÖZER, METİN; ERDEM, MURAT (ROYAL SOC CHEMISTRY, 2020)
Novel 4,4 '-(((2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)bis(2-methylpropane-2,1-diyl))bis(oxy)) (SUBO) bridged ball-type metallophthalocyanines were synthesized starting from 4,4 '-(((2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)bis(2-methylpropane-2,1-diyl))bis(oxy))diphthalonitrile with convenient metal salts in 2-N,N-dimethylaminoethanol. A new bisphthalonitrile compound was obtained from 2,2 '-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)bis(2-methylpropan-1-ol) and 4-nitrophthalonitrile in acetonitrile at reflux temperature in the presence of potassium carbonate as a catalyst. The structural characterization of the compounds was performed by elemental analysis, and infrared, ultraviolet-visible and matrix-assisted laser desorption/ionization time-of-flight mass spectroscopic methods. Nonlinear absorptions of the phthalocyanine complexes were measured using the Z-scan technique with 7 ns pulse duration at a 532 nm wavelength. It is obvious that ball-type copperphthalocyanine has a high nonlinear absorption coefficient and imaginary component of the third-order susceptibility compared to other complexes. Therefore, ball-type copperphthalocyanine can be regarded as a very good candidate for optical limiting applications. Density functional theory was used for geometry optimizations and time-dependent density functional theory calculations of electronic transitions in order to compare with the experimental results. Molecular orbital and nonlinear optical analyses were also performed with density functional theory at the CAM-B3LYP/6-31G(d,p)/LANL2DZ level. The nonlinear optical analyses show that ball-type copperphthalocyanine has significantly better nonlinear optical properties in comparison to a common reference compound, urea.
Keywords: SUBSTITUTED METALLOPHTHALOCYANINES; ELECTROCATALYTIC ACTIVITY; ZINC-PHTHALOCYANINE; SENSING PROPERTIES; LIMITING PROPERTY; OXYGEN REDUCTION; HIGH-PERFORMANCE; ABSORPTION; METALS